THU0753-HPR Predicting the future development of spondyloarthritis among patients with idiopathic acute anterior uveitis using real-world data. (15th June 2017) - Haroon, M; Betts, KA; Mu, F; Skup, M; Anderson, JK; Joshi, AD
Abstract : Background: Previous studies have suggested an association between idiopathic acute anterior uveitis (AAU) and spondyloarthritis (SpA), including showing that at least 40% of AAU patients have undiagnosed SpA. However, the clinical factors to predict the incident diagnosis or future development of SpA remain poorly recognized. Objectives: The objectives of this study were: 1) to describe the patient characteristics of AAU patients with and without SpA diagnosis, and 2) to identify the predictive factors of SpA diagnosis among AAU patients using real-world data. Methods: Adult patients with at least one diagnosis of AAU (ICD-9-CM: 364.01 or 364.02) were selected from a large US insurance claims database (01/01/2008–06/30/2015). The first AAU diagnosis was defined as the index date. Patients were required to have at least 6 months of continuous data availability before the index date. Patients with intraocular surgery, penetrating or blunt eye trauma, or a diagnosis of rheumatoid arthritis or SpA on or prior to the index date were excluded. Potential predictive factors for subsequesnt diagnosis of SpA included demographic characteristics, type of AAU (primary [first diagnosis] vs. recurrent), SpA-related comorbidities, and healthcare resource utilization prior to the index date. Factors predictive of SpA diagnosis were selected into a multivariable Cox proportional hazards model based on statistical significance and clinical relevance. Hazards ratios (HR) and p-values were estimated for each factor. Results: A total of 48, 822 patients with AAU were included, and among them, 1, 032 patients were newly diagnosed with SpA during the follow-up period which was 24 months on average. Patients with SpA were younger (45.7 vs. 50.4 years), more likely to be male (52% vs. 42%), more likely to have recurrent AAU (44% vs. 29%), back pain (21% vs. 13%), SpA-related comorbidities including inflammatory bowel disease (IBD) (4% vs. 1%) and psoriasis (3% vs. 1%), and more likely to use corticosteroids (45% vs 40%). Predictive factors in the final Cox model were: male vs. female (HR=1.55; p-value<0.01), age<45 vs. ≥45 years old (1.65; <0.01), recurrent vs. primary AAU (1.94; <0.01), back pain under age 45 vs. no back pain (1.90; <0.01), back pain above age 45 vs. no back pain (1.46; <0.01), psoriasis (5.16; <0.01), IBD (2.50; <0.01), chiropractor/physical therapist visits (1.29; 0.01), conjunctivitis (1.23; 0.02), nonsteroidal anti-inflammatory drugs use (1.44; <0.01), use of conventional synthetic disease-modifying anti-rheumatic drugs (1.32; 0.05), joint pain (1.14; 0.19), imaging test use (1.03; 0.74), corticosteroids use (1.07; 0.33), and enthesitis/heel pain (1.13; 0.36). When sacroiliitis was included in the model, results remained largely similar. Conclusions: There are significant differences among isolated AAU patients and AAU patients that developed SpA later. The most predictive factors of SpA diagnosis were male, age<45 years, recurrent AAU, back pain, and other extra-articular manifestations of SpA such as IBD and psoriasis. Since delayed diagnosis is common among SpA patients, identifying such predictive factors can help inform risk stratification. Disclosure of Interest: M. Haroon Grant/research support from: AbbVie and Pfizer, K. Betts Consultant for: AbbVie, F. Mu Consultant for: AbbVie, M. Skup Employee of: AbbVie, J. Anderson Employee of: AbbVie, A. Joshi Employee of: AbbVie